Activity of oxidative processes and the state of the redox regulating system in tumor tissue in skin cancer - I. A. Goroshinskaya; E. M. Frantsiyants; N. I. Larina; Yu. V. Przhedetskiy; I. V. Kaplieva; L. A. Nemashkalova; V. A. Bandovkina; V. V. Pozdnyakova; V. Yu. Przhedetskaya (Исследования и практика в медицине)
Purpose of the study. To study the intensity of lipid peroxidation (LPO) and the activity of antioxidant protection components in tumor tissues, peritumoral zone and conditionally healthy skin tissue in basal cell carcinoma, depending on the type of tumor growth, gender of patients, and the presence of concomitant diseases.Materials and methods. Tissues from 34 patients with basal cell carcinoma (BCC) were studied, including 17 women (10 with superficial tumor growth and 7 with solid growth) and 17 men (5 and 12 patients, respectively). We used skin flaps obtained during operations on 12 men and 10 women without malignant pathology (“norm”) as a comparison material. The content of malondialdehyde (MDA), diene conjugates (DC), superoxide dismutase (SOD) activity and total peroxidase activity (TPA) were determined. Statistical processing of the results was carried out using the Statistica 10.0 program.Results. In women, the level of MDA was increased in all tissues: with superficial growth of BCC by 2.1–2.5 times (p ≤ 0.05), with solid growth by 1.6–2.1 times (p < 0.05) relative to the “norm”. In men with superficial growth, an MDA increase by 3.2 and 3.1 times in tumor tissue and conditionally healthy tissue was observed (p < 0.02), and no increase in MDA in the tumor was detected in 11 of 12 patients with solid growth. An increase in DC (on average 2–5 times) in BCC patients with concomitant hypertension and diabetes mellitus was observed mainly in women. Activation of SOD in tumor tissue, to a greater extent in men (2.4 times with superficial growth and 1.7 times with solid growth, p < 0.05 relative to conditionally healthy tissue), can be considered as a mechanism of antiradical protection of the tumor.Conclusions. An increase in the level of MDA in BCC was observed in tumor and nearby tissues in women with both types of growth, in men only with superficial growth. Analysis of individual characteristics of LPO indicators in patients with skin carcinoma revealed a dependence of the severity of the increase in MDA and especially DC on the presence of concomitant pathology (hypertension, diabetes mellitus).